Penerapan Community Based Tourism Di Desa Wisata Sudaji Kabupaten Buleleng Bali - Dhiya Ulhaq Fauzan; Dianasari, Dewa Ayu Lily; Subrata, I Made (Journal of Applied Science in Tourism Destination, 2025)
Sudaji Tourism Village is one of the community-based tourist destinations located in Buleleng Regency, Bali, known for its natural beauty and rich cultural heritage. Its main attractions include trekking to scenic waterfalls and experiencing local cultural traditions such as the Ngusaba Bukakak ceremony. The village adopts the concept of Community-Based Tourism (CBT), which emphasizes economic, socio-cultural, and environmental dimensions. This study aims to analyze the implementation of CBT in Sudaji Tourism Village and to identify the challenges encountered during its application. A qualitative research approach was employed, with data collected through observation, in-depth interviews, documentation, and literature study. Informants were selected using purposive sampling based on their involvement in the village tourism management. The findings indicate that from an economic perspective, CBT implementation contributes to increased income and employment opportunities for the local community, including through homestay businesses, food stalls, tour guiding, and entrepreneurship. In terms of socio-cultural aspects, capacity-building training and the preservation of local traditions—such as the Ngusaba Bukakak ceremony and traditional Balinese musical instruments (gamelan and rindik)—play a key role. Environmentally, CBT practices are reflected in community initiatives such as regular communal clean-ups, tree planting along tourist access roads, and local waste management. This study underscores the importance of active community participation in fostering sustainable tourism development. Keywords: Community Based Tourism, Tourism Village, Economy, Socio-Culture, Environment.